Perception of hybrid threats by students of selected universities and building effective resistance against their effects - Antonín Korauš; Lucia Kurilovská; Patrícia Krásná; Miroslav Gombár; Patrik Javorčík (Entrepreneurship and Sustainability Issues, 2024)
The issue of hybrid threats is an ongoing topic that resonates with the professional and the lay public. More and more in the scope of professional discussions, we come across the definition and specification of circumstances in which the significant signs of hybrid threats are discussed and the threat they pose to society are pointed out. The study reflects the need to know and specify the understanding of “hybrid threats”. It presents the results of a survey that was conducted to determine how students of two universities in the Slovak Republic (the Police Force Academy in Bratislava and the Faculty of Management, Economics and Business of the University of Prešov in Prešov) perceive and whether they even know the term “hybrid threats” itself. A significant moment in the orientation of young people to security aspects is knowledge of the definition of this term among young students who are preparing for a profession and who will form the future of the international community. Therefore, only a precise specification of the concept and a definition of the distinct elements for building effective resistance to hybrid threats at the national and international level, specifically in individual countries, will help us maintain a sense of security among individual members of society. The content of the study is constructed to fulfil the primary goal, which is to determine and present the perception of the concept of “hybrid threats” among university students, as well as to present elementary concepts associated with the issue of hybrid threats and a selected element supporting resistance to hybrid threats at the national level – strategic communication. The proposed findings are based on quantitative and qualitative research conducted within the national project “Increasing Slovakia’s resilience to hybrid threats by strengthening public administration capacities” and reflect on the current needs of the security environment at both the national and international levels. The research was conducted between May and September 2023 to obtain quantitative and qualitative indicators.